Pai-acompanhante e a sua compreensão sobre o processo de nascimento do filho - Danubia Mariane Barbosa Jardim (2009)
This is a qualitative study, fundament on the Comprehensive Sociology of Michel Maffesoli, with the objective of understanding the father experience in labor and birth. The research scenery was the Centro de Parto Normal Dr David Capistrano (CPN) Unidade intra-hospitalar of Hospital Sofia Feldman (HSF), which belongs to the Fundação de Assistencia Integral à Saúde/Hospital Sofia Feldman (FAIS/HSF), non-governmental institution, philanthropist, focused in womans and newborns health. The subjects were 14 fathers who accompanied the labor and birth in the CPN, being the first child of the couple and both parents without children from previous marriages. The data gathering was done via a semi-structured script. To analyze the data, content analysis according to Bardin (2004) and Minayo (2008) was used. From the analyzed three empiric categories were created: 1. A son is born, a father is born, 2. The support of the father during labor, 3. The neutrality of birth. The first category is about two aspects lived by the father during labor: first the perception of the labor pain, seen as a necessary suffering to the labor, which He can experience with the mother; the second is about contradictory feelings, facing the fear of the unknown and the emotions this moment brings. The second category reveals the support of the father to the mother. The third category emphasizes the meanings given by the father to natural labor, describing the process from a male point of view, and highlights the encounters with health professionals as a user of the Health System. The study made it possible to understand the comprehension of man regarding labor, pointing to new discussions about fatherhood and the importance of his presence in the labor.